Capacitive proximity floor sensing system for elderly tracking and fall detection - Arshad, Atika; Khan, Sheroz; Alam, A. H. M. Zahirul; Ismail, Ahmad Fadzil; Tasnim, Rumana (Institute of Electrical and Electronics Engineers Inc., 2018)
With the advent and progress of technology, care of senior individuals requires spontaneous and timely decisions to be made so that life protecting and saving therapy can be delivered promptly. Research shows that assistive technology can provide systems to aid in the prevention and detection of injuries to seniors, leading to a faster response from monitoring personnel. Falls make one of the major injuries caused to seniors whereby they are often unable to receive proper and timely support. This work reports the preliminary results on the development of a capacitive-based sensing system for monitoring of inhabitants living on their own in elderly homes. The tracking and fall monitoring of elderly is based on floor-sensing model equipped with an occupancy mechanism. To perceive and recognise the behavioural changes of an individual on daily basis, integrated sensors are designed and developed using capacitive proximity sensing approach. The weight of a person exerts a pressure on the sensor, indicating the occupancy of the sensor spot when a threshold value set for this purpose, is exceeded. To begin with, the occupancy sensing floors are equipped with sensors and later integrated into the environment, which aims at providing assistive service for continuous diagnosis of a person’s health, hence keeping track of an individual’s behavioural patterns.